Pineapple Liquid Waste Indigenous Bacteria Consortium for Improving the Quality of Sediment-Based Organic Fertilizers for Shrimp Ponds - Beny Saputra; Agus Sutanto; Hening Widowati (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2026)
Shrimp pond sediment is a biosolid waste that can degrade water quality but contains organic matter and nutrients that can be reused as organic fertilizer. Liquid pineapple waste (LCN) harbors indigenous bacteria that can serve as composting starters. This study evaluated the effectiveness of LCN-derived consortia in improving the quality of shrimp pond sediment–based organic fertilizer. A completely randomized design with six treatments (control, P1–P5) and five replications was used. The consortia were aerobically fermented for 30 days with sediment, leaf litter, rice husk charcoal, and LCN. Total N, P₂O₅, K₂O, organic C, C/N ratio, pH, and moisture content were analyzed using one-way ANOVA and Tukey's test (α = 0.05). The consortia significantly affected (p < 0.05) most parameters, except moisture content. Treatment P5 (15 isolates) produced the highest total N (3.44%), K₂O 2.70%, C/N ratio 9.47, pH 6.2, and organic C around 32–33%, whereas P3 (9 isolates) showed the highest P₂O₅ (2.39%); these values generally met or approached the Indonesian standard for organic fertilizer (Permentan No. 261/2019). LCN-based consortia thus have potential as local starters to improve shrimp pond sediment–based organic fertilizer, although further studies on salinity, heavy metals, and field performance are needed.